Fiscal consolidation What factors determine the success of consolidation efforts? - Molnár, Margit (OECD Publishing, 2012)
The global economic and financial crisis exacerbated the need for fiscal consolidation in many OECD countries. Drawing lessons from past episodes of fiscal consolidation, this study investigates the economic environments, political settings and policy measures conducive to fiscal consolidation and debt stabilisation using probit, duration, truncated regression and bivariate Heckman selection methods. The empirical analysis builds on the earlier literature and extends it to include new aspects that may be of importance for consolidating governments. The empirical analysis confirms previous findings that the presence of fiscal rules - expenditure or budget balance rules - is associated with a greater probability of stabilising debt. Crucial in determining the causal link behind the association, the results also reveal an independent role for such rules over and above the impact of preferences for fiscal prudence. Also, while the analysis confirms that spending-driven adjustments visà- vis revenue-driven ones are more likely to stabilise debt, it also reveals that large consolidations need multiple instruments for consolidation to succeed. Sub-national governments, in particular state-level governments can contribute to the success of central government consolidation, if they co-operate. To ensure that state-level governments do co-operate, having the right regulatory framework with the extension of fiscal rules to sub-central government levels is important
Keywords: Economics